The rising sun : - Toland, John (Random House, 1970)
This Pulitzer Prize–winning history of World War II chronicles the dramatic rise and fall of the Japanese empire, from the invasion of Manchuria and China to the atomic bombing of Hiroshima and Nagasaki. Told from the Japanese perspective, The Rising Sun is, in the author’s words, “a factual saga of people caught up in the flood of the most overwhelming war of mankind, told as it happened—muddled, ennobling, disgraceful, frustrating, full of paradox.”